Characterization of natural genetic variation in tomato (Solanum lycopersicum) for root ammonium uptake - Ragazzo, Gabriel de Oliveira (2021)
Most cultivated plants, and especially tomato (Solanum lycopersicum), require large amounts of nitrogen (N) to achieve high commercial yields. Consequently, excessive quantities of the costly N-based fertilizers are supplied during crop cultivation. The investigation of the natural genetic variability for N uptake may help to design genetic strategies to improve N use efficiency (NUE) in tomato and, ultimately, decrease the amount of applied fertilizers. In plants, ammonium is the preferred source of N and is transported through proteins of the AMMONIUM TRANSPORTERS family (AMTs). Thus, the objective of this work was to identify and characterize AMTs, as well as possible regulations that alter the ammonium uptake in tomato. In a genomic survey, eight AMTs were identified in tomato, of which four had not been described before. The SlAMTs showed significant differences in expression between the plant tissues, indicating possible specific functions for each gene. In root, SlAMT1.1 was the most expressed and is described as the main responsible for ammonium uptake in several species. Diversity analysis indicated the presence of great variability in the SlAMT1.1 sequence between tomato accessions and wild Solanum species (section Lycopersicon). A study of 15N-labeled ammonium uptake kinetics under different N availability was carried out among the genotypes S. lycopersicum cv. M82, S. pimpinellifolium, S. habrochaites, and S. chmielewskii. When N was supplied at sufficient levels, S. chmielewskii showed a greater 15N-ammonium influx, which correlated with a higher level of SlAMT1.1 expression in this genotype. During ammonium resupply, S. habrochaites and S. chmielewskii genotypes showed less inhibition of the 15N-ammonium uptake process when compared to S. lycopersicum cv. M82 and S. pimpinellifolium. The expression levels suggest a differential allosteric regulation of SlAMT1.1 in these genotypes. These results suggest that variability in the SlAMT1.1 gene among tomato genotypes can provide different patterns of protein activity and gene expression under different N conditions. Finally, a genomic wide association study (GWAS) using 31 tomato accessions was carried out and indicated the presence of a SNP (GC) in the 3\' UTR region of a 14-3-3 gene, which seem necessary to modulate the expression of SlAMT1.1. Further evidences implied that this locus is associated with the signaling by brassinosteroids, although further studies are necessary to better describe this mechanism. In summary, natural genetic variation in tomato has great potential for breeding new cultivars with greater efficiency in the use of nitrogen